POLA KOMUNIKASI TEMAN SEBAYA PADA PENYINTAS ORANG DENGAN GANGGUAN JIWA - Zardy, Faiz Atharian; Huda, Anam Miftakhul (The Commercium, 2024)
This research aims to find out how peers interact with people with mental disorders (ODGJ). These interactions develop communication patterns. This research uses a qualitative approach with phenomenological methods to gain an in-depth understanding of ODGJ's life experiences in interacting with their surrounding environment, especially their peers. The peers as informants were friends from childhood until this research was conducted. This research found three main themes of chats: hobbies (playing online games), personal (family stories and personal experiences), and random (joking around without a specific theme). Peers show two communication behaviors: restraint and candidness. Self- restraint is used to maintain the emotional stability of ODGJ by choosing words and gestures that are not offensive, while the actual behavior shows natural interactions without any restrictions, often in the context of joking. Peers feel responsible for supporting ODGJ toward recovery even though they have limited knowledge about mental disorders. This research highlights the importance of social support from peers and provides recommendations for expanding research further with more diverse sources and data.